1977
DOI: 10.1002/ps.2780080607
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of resistance of houseflies (Musca domestica L.) to pyrethroids. I. Knock‐down resistance

Abstract: Knock‐down resistance in Musca domestica, which provides cross‐resistance between DDT and pyrethroids, has been genetically separated from three different resistant populations. After careful purification of each factor, the cross‐over rates between them and the visible mutants brown body and green eye were estimated. This indicated that these factors are probably identical. The influence and implications of the knock‐down resistance factor, kdr, on the total resistance of populations that include it are brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 12 publications
2
50
0
Order By: Relevance
“…This unusual negative crossresistance suggests that 7V-alkylamides could combat resistance caused by super-kdr which in adult houseflies delays the onset of knockdown and decreases kill by DDT and its analogues, and by pyrethroids.10) Kdr resistance, which is non-metabolic, and therefore unaffected by the usual DDT or pyrethroid synergists, 12) is associated with decreased sensitivity of the insect nervous system to these insecticides at the level of the Na+ channel within the lipophilic environment of the membrane adjacent to or near the Na+ gate protein.13) The differential toxicity of iV-alkylamides between the S and super-kdr strains was maintained after the flies had been treated with synergist. In consequence, the synergised LD50 for He against the super-kdr strain is about a quarter that of the most effective pyrethroid/synergist combination.…”
Section: Resultsmentioning
confidence: 99%
“…This unusual negative crossresistance suggests that 7V-alkylamides could combat resistance caused by super-kdr which in adult houseflies delays the onset of knockdown and decreases kill by DDT and its analogues, and by pyrethroids.10) Kdr resistance, which is non-metabolic, and therefore unaffected by the usual DDT or pyrethroid synergists, 12) is associated with decreased sensitivity of the insect nervous system to these insecticides at the level of the Na+ channel within the lipophilic environment of the membrane adjacent to or near the Na+ gate protein.13) The differential toxicity of iV-alkylamides between the S and super-kdr strains was maintained after the flies had been treated with synergist. In consequence, the synergised LD50 for He against the super-kdr strain is about a quarter that of the most effective pyrethroid/synergist combination.…”
Section: Resultsmentioning
confidence: 99%
“…Similarities between the kdr and super-kdr traits, such as their broad cross-resistance to all pyrethroids, DDT, and some DDT analogues and their placement onto the same linkage group, have led to the speculation that super-kdr is allelic to kdr and other independently isolated alleles of the kdr locus (6,7,18 (1994) resolution of about 1 map unit. These results provide genetic evidence consistent with the presumed allelism of super-kdr and the kdr locus.…”
Section: <-----Primer B2---------tctcatgacc Caagatttct Gggaggatct Gtatcagcac Gtgctgcaagmentioning
confidence: 99%
“…This type of resistance, termed "knockdown resistance," results from an intrinsic reduction in the sensitivity of the insect nervous system to the toxic effects of these compounds (3). Knockdown resistance was first described and isolated as a recessive genetic trait, named kdr, in strains of DDT-resistant house flies (Musca domestica L.) (4)(5)(6). Subsequent studies identified other nerve-insensitivity traits (designated superkdr) that confer higher levels of resistance to DDT and pyrethroids (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, (2000b) first reported that head lice from Massachusetts and Florida were resistant to a pyrethroid, permethrin, and exhibited in vivo responses in behavioral bioassays that are consistent with knockdown resistance. Knockdown resistance (kdr) is a heritable trait associated with nerve insensitivity to DDT, the pyrethrins and the pyrethroids, that was first discovered in house fly, Musca domestica (Busvine, 1951;Farnham, 1977). Phenotypically similar kdr-like traits have been subsequently identified in other species of resistant insects (Oppenoorth, 1985;Soderlund, 1997).…”
Section: Introductionmentioning
confidence: 99%